Correction to: Pediatric procedural sedation and analgesia in the emergency department: surveying the current European practice - Cyril Sahyoun; Aymeric Cantais; Alain Gervaix; Silvia Bressan; Ruth Löllgen; Baruch Krauss; Annick de Jaeger; Marianne Sjølin Frederiksen; Gérard Chéron; Katharina Röher; Florian Hoffmann; László Fodor; et al. (European Journal of Pediatrics, 2021)
A correction to this paper has been published: 10.1007/s00431-021-03980-w